Differences in ichthyofauna feeding habits among lateral lagoons and the river channel in a large reservoir - Ferrareze,M. (2015)
In this study, we investigated differences in feeding habits of small-sized ichthyofauna among lateral lagoons and the river channel in a large reservoir. The study was performed in four lagoons and in one sampling site of the main channel in Rosana Reservoir, Paranapanema River, Brazil. The samples were taken in September and November of 2004 and in January, March, May, and August of 2005. Fish were sampled with a 7.5 m2 hand net. Five manual throws were made toward aquatic macrophytes stands. The sampling design favored the collection of small-sized fish fauna (juveniles/small-sized species). The stomach contents of 42 species were analyzed. A total of 183 different items were consumed by fish. These items were grouped in 11 food categories, which were used to classify fish into seven trophic guilds. Aquatic insects were consumed by 32 species and were the predominant feeding item. In the river, the most consumed items were aquatic insects, cladocerans, and phytoplankton, whereas in the lagoons aquatic insects, copepods, and cladocerans were the main items. By comparing each trophic guild, the number of insectivores, algivores, and zooplanktivores species was higher in the lagoons than in the river, and the opposite was found only for omnivore fish. Low niche width in all sites indicates high trophic specialization and low niche overlap between pairs of species. Fish assemblage in the lateral lagoons presents feeding habits distinct from those of the river species, indicating that the coexistence and high abundance of small-sized fish in the sampling sites are explained by their high feeding adaptability, which includes a tendency toward dietary specialization, low feeding overlap, and resource partitioning, along with different temporal resource uses.